Identification and functional characterization of the RPP13 gene family in potato (Solanum tuberosum L.) for disease resistance - Baoqi Yuan; Chuang Li; Qingfeng Wang; Qi Yao; Xiaowei Guo; Yuhang Zhang; Zhongwei Wang (Frontiers in Plant Science)
Potato (Solanum tuberosum L.), as the world’s fourth largest food crop, plays a crucial role in ensuring food security through its disease resistance. The RPP13 gene family is known to play a pivotal role in plant disease resistance responses; however, its specific functions in potato remain unclear. In this study, we conducted the first comprehensive identification and analysis of 28 RPP13 gene family members in potato, examining their gene structures, chromosomal locations, expression patterns, and functional characteristics. Gene structure analysis revealed that most members contain the typical CC-NBS-LRR domains, with exon numbers ranging from 1 to 6. Phylogenetic analysis grouped these genes into four evolutionary clades, indicating a high level of conservation. Cis-regulatory element analysis identified that the promoter region of StRPP13-26 is enriched with pathogen-responsive elements such as the WUN-motif and MYC, suggesting its potential role in disease defense. Expression pattern analysis showed that StRPP13-8, StRPP13-10, and StRPP13-23 are highly expressed in various tissues, indicating their involvement in basic physiological functions, whereas StRPP13-6 and StRPP13-25 are mainly induced under specific pathogen infection conditions. Transcriptome and qRT-PCR analyses further revealed functional divergence of the RPP13 gene family in response to potato scab disease. Notably, StRPP13-11 was significantly downregulated in both resistant and susceptible cultivars, suggesting its crucial role in the early stages of pathogen recognition. Subcellular localization experiments showed that the StRPP13-11 protein is localized in the chloroplast. Combined with transcriptome-based functional enrichment analysis, this finding implies that StRPP13-11 may participate in disease defense by regulating photosynthesis-related genes and the dynamic balance of reactive oxygen species within the chloroplast. This study provides new insights into the potential functions of the RPP13 gene family in potato disease resistance mechanisms, offering valuable genetic resources and theoretical support for future disease-resistant breeding programs.